Regulasi Emosi pada Emerging Adulthood dengan NSSI: Peran Keberfungsian Keluarga dan Self Compassion - Hanifah Indri Nuryamin; Dinda Aisha; R Yuwono Pratomo (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Individuals with a history of Non-Suicidal Self-Injury (NSSI) frequently utilize self-harm as a maladaptive coping mechanism, largely due to severe difficulties in emotion regulation. This vulnerability is particularly pronounced during emerging adulthood, a developmental period characterized by significant psychosocial transitions. Consequently, this study aims to examine the simultaneous and partial influence of family functioning and self-compassion on emotion regulation among emerging adults with a history of NSSI in Karawang Regency, Indonesia. Employing a quantitative cross-sectional correlational design, the study recruited a sample of 204 participants through convenience sampling. Data were collected using three standardized instruments: the Difficulties in Emotion Regulation Scale-Short Form (DERS-SF), the McMaster Family Assessment Device-General Functioning Subscale (FAD-GF), and the Self-Compassion Scale (SCS). The collected data were subsequently analyzed using multiple linear regression techniques via SPSS version 26. The findings indicated that, partially, family functioning did not significantly predict emotion regulation. In contrast, self-compassion emerged as a significant predictor. Collectively, both family functioning and self-compassion accounted for 19.1% of the total variance in emotion regulation among the participants. In conclusion, self-compassion serves as a more dominant protective factor in predicting emotion regulation for individuals with an NSSI history compared to family functioning. These findings suggest that clinical and psychological interventions tailored for this demographic should strongly prioritize fostering self-compassion to improve emotional resilience and reduce reliance on self-injurious behaviors.